BUSINESS PLANNING OF TRADE ENTERPRISES IN THE CONTEXT OF ENSURING THEIR COMPETITIVENESS - HARVAT, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In this article examines the role of business planning of trading enterprises in ensuring their competitiveness. The peculiarities of planning the activities of a trading enterprise are determined. The trading enterprises are characterized by their own "planning philosophy", as the value chain is based on close cooperation with local suppliers, efficient logistics, adaptation to consumer needs, and high service standards. It is established that business planning: provides a strategic vision for the development of trading activities and facilitates rapid adaptation to the variability of the market economy; promotes more efficient use of resources; provides the ability to manage risks; promotes innovation in trading activities; allows for in-depth analysis of competitors; ensures improved organizational effectiveness.In terms of gross domestic product, trade enterprises rank third, accounting for 12.6% of the country's total gross domestic product. Therefore, ensuring their competitiveness is quite important. The competitiveness of an enterprise is achieved by creating competitive advantages in comparison with other competing enterprises. The implementation of business planning will ensure the identification of competitive advantages, determination of the level of sustainability, and specification of development strategies.Business planning is a necessary tool for the successful development of trading enterprises in conditions of fierce competition. It allows not only to survive, but also to achieve sustainable competitive advantages. In order to implement the tasks assigned to the business plan, it is advisable: regularly review and adjust the business plan; use modern business planning tools and methods; involve external experts and highly professional employees of the enterprise in the planning process.
Keywords: economic development; competitiveness; business planning; trade enterprises